Association of Genetic Polymorphisms with Risperidone Treatment Response in Schizophrenia: A Review - Gina Sabila; Rano K. Sinuraya (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Schizophrenia is a severe mental disorder characterized by positive, negative, and cognitivesymptoms that affect the quality of life. Risperidone is widely known as second-generation antipsychoticthat is effective to treat schizophrenia. Unlike the first-generation antipsychotic, risperidone has a lowerimpact on the extrapyramidal adverse effect. However, individually, the risperidone treatment response maybe different caused by the genetic polymorphisms. This review aims to examine the association of geneticpolymorphisms with risperidone treatment response in schizophrenia.Method: The review was conducted using the Pubmed database and 49 articles included in this reviewamong 80 articles obtained in an initial search. The result showed genetic polymorphisms which affectsrisperidone therapy include DRD2, genetic polymorphisms on serotonin, cytochrome P450, BDNF, COMT,and ABCB1. Those polymorphisms might increase or decrease pharmacokinetics and pharmacodynamicprofile of risperidone. In addition, genetic polymorphisms also contributed to the risk of metabolic syndromeand hyperprolactinemia induced by risperidone treatment.Conclusion: Based on those findings, several genetic polymorphisms had an association with therapeuticoutcomes and side effect after risperidone treatment. Genetic polymorphisms screening may be useful fordrug choices or dosage adjustment that safer and effective for patients.